Toward a Race-Conscious Critique of Mental Health-Related Exclusionary Immigration Laws - Kashyap, Monika Batra (2021)
This Article employs the emergent analytical framework of Dis/ability Critical Race Theory (DisCrit) to offer a race-conscious critique of a set of immigration laws that have been left out of the story of race-based immigrant exclusion in the United States—namely, the laws that exclude immigrants based on mental health-related grounds. By centering the influence of the white supremacist, racist,and ableist ideologies of the eugenics movement in shaping mental health-related exclusionary immigration laws, this Article locates the roots of these restrictive laws in the desire to protect the purity and homogeneity of the white Anglo- Saxon race against the threat of racially inferior, undesirable, and unassimilable immigrants. Moreover, by using a DisCrit framework to critique today’s mental health-related exclusionary law, INA § 212(a)(1)(A)(iii), this Article reveals how this law carries forward the white supremacist, racist, and ableist ideologies of eugenics into the present in order to shape ideas of citizenship and belonging. The ultimate goal of the Article is to broaden the conceptualization of race-based immigrant exclusion to encompass mental health-related immigrant exclusion, while demonstrating the utility of DisCrit as an exploratory analytical tool to examine the intersections of race and disability within immigration law